TaSnRK2.9, a Sucrose Non-fermenting 1-Related Protein Kinase Gene, Positively Regulates Plant Response to Drought and Salt Stress in Transgenic Tobacco - Jialu Feng; Lianzhe Wang; Lianzhe Wang; Yanan Wu; Qingchen Luo; Yang Zhang; Ding Qiu; Jiapeng Han; Peipei Su; Zhiyong Xiong; Junli Chang; Guangxiao Yang; et al. (Frontiers in Plant Science, 2019)
Sucrose non-fermenting 1-related protein kinase 2 (SnRK2) family members play crucial roles in plant abiotic stress response. However, the precise mechanism underlying the function of SnRKs has not been thoroughly elucidated in plants. In this research, a novel SnRK2 gene, TaSnRK2.9 was cloned and characterized from common wheat. The expression of TaSnRK2.9 was upregulated by polyethylene glycol (PEG), NaCl, H2O2, abscisic acid (ABA), methyl jasmonate (MeJA), and ethrel treatments. TaSnRK2.9 was mainly expressed in wheat young root, stamen, pistil, and lemma. Overexpressing TaSnRK2.9 in transgenic tobacco enhanced plants’ tolerance to drought and salt stresses both in young seedlings and mature plants with improved survival rate, seed germination rate, and root length. Physiological analyses suggest that TaSnRK2.9 improved antioxidant system such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and glutathione (GSH) to reduce the H2O2 content under drought or salt stress. Additionally, TaSnRK2.9 overexpression plants had elevated ABA content, implying that the function of TaSnRK2.9 may be ABA-dependent. Moreover, TaSnRK2.9 increased the expression of some ROS-related, ABA-related, and stress-response genes under osmotic or salt treatment. TaSnRK2.9 could interact with NtABF2 in yeast two-hybrid assay, and increased the expression of NtABF2 under mannitol or NaCl treatment in transgenic tobacco plants. In conclusion, overexpression of TaSnRK2.9 in tobacco conferred plants tolerance to drought and salt stresses through enhanced ROS scavenging ability, ABA-dependent signal transduction, and specific SnRK-ABF interaction.